Hay Yield, Quality Traits and Interspecies Competition of Forage Pea - Triticale Mixtures Harvested At Different Stages - Aşcı, Özlem Önal; Acar, Zeki; Arıcı, Yeliz Kaşko (My University, 2015)
The present study was conducted in two years under ecological conditions of Ordu Province to investigate the effects of different mixture ratios and harvest stages on hay yield, some quality traits and interspecies competition of forage pea-triticale mixtures. Leafed (ü) and semi-leafless (U) forage pea (Pisum sativum L.) cultivars and triticale (xTriticosecale Wittmack) were sown as monocrops and in different forage pea:triticale mixture ratios (75:25, 50:50, 25:75) and harvested at booting and milk-dough stage of triticale. Considering the total digestible dry matter and crude protein yields of the treatments together, it was observed that T75:ü25, T50:ü50, T75:U25 mixtures harvested at milk-dough stage of triticale produced high yields. In addition, leafed forage pea was found to be more aggressive than semi-leafless cv. in all mixtures.
Keywords: Ziraat Mühendisliği